2015
DOI: 10.15537/smj.2015.6.11501
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of medical students with simulation based learning

Abstract: Objectives:To evaluate medical students’ satisfaction with simulation based learning strategy (SBL).Methods:A cross-sectional survey was conducted between October and November 2013 at the College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia. All third and fourth year medical students (n=185) both males and females were included. A self-developed questionnaire on the effect of SBL was used. Items included were related to knowledge, skill, environment, resources, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
33
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 21 publications
13
33
1
2
Order By: Relevance
“…This was demonstrated with the study result which shows that, out of the 13 questions in the survey, the average percent agreement was 77.5%. These results agree with several previous studies which reported that HFS improves students' level of self-confidence and satisfaction with their training (Agha, Alhamrani, & Khan, 2015;Omar,2015;&Kim, 2016).Furthermore, the item "My instructor did a good job of teaching the simulat ion " got the highest response (83.4%) of the questions that measure satisfaction; "I was taught the simu lation with the aid of 7 useful resources" got the highest response (83.0%) of the questions that measure self-confidence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was demonstrated with the study result which shows that, out of the 13 questions in the survey, the average percent agreement was 77.5%. These results agree with several previous studies which reported that HFS improves students' level of self-confidence and satisfaction with their training (Agha, Alhamrani, & Khan, 2015;Omar,2015;&Kim, 2016).Furthermore, the item "My instructor did a good job of teaching the simulat ion " got the highest response (83.4%) of the questions that measure satisfaction; "I was taught the simu lation with the aid of 7 useful resources" got the highest response (83.0%) of the questions that measure self-confidence.…”
Section: Discussionsupporting
confidence: 93%
“…With simulation, learners are afforded the opportunity to synthesize cognitive, affective and psychomotor skills with various clinical scenarios in a safe and supportive environment (Fong, 2013;Agha, Alhamrani, & Khan, 2015). Through highfidelity simulation, students are also afforded the opportunity to apply the theoretical knowledge gained during lectures, to learn from errors without putting patients in danger, to learn from their peers, and to bridge the gaps between knowledge and practice (Lewis, 2012;Onello& Regan, 2013;Abelsson&Bisholt,2017).In addition, HFS helps acquire advanced skills, which can be improved and synthesized with interactive repeated scenarios (Decker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the control group point out approximately same level of knowledge throughout the study period. In this context This finding is supported by Agha S. et al, (2015) (19) & Monod C. et al ,(2014) (20) they endorse the use of simulation training as a preferred educational technique, notably they elaborated that training based on patient simulators and real patients simulation, help students to promote cognitive knowledge, technical skills, critical thinking skills and reasoning decision making and confidence during simulation sessions for clinical practice, which provide conducive learning environment and improves communication and teamwork in emergency situations.…”
Section: Effect Of a Medium Fidelity Simulation Based Training On Nursessupporting
confidence: 69%
“…The overwhelmingly positive response and request for further simulation by both pre-clinical and clinical students is consistent with previous findings (Agha, Alhamrani & Khan, 2015;Paskins & Peile, 2010;Gordon et al, 2001) and understandable given the high value students place upon clinical exposure. However, the unique peer learning experience and opportunity to manage an acute clinical case with colleagues at different levels highlights the additional educational advantages that occur by combining year groups.…”
Section: Resultssupporting
confidence: 89%